DOI: 10.3384/diss.diva-150953
|View full text |Cite
|
Sign up to set email alerts
|

Shaped for beauty: Vocational and gendered subjectivities in private education for the beauty industry

Abstract: Eleonor Bredlöv Shaped for Beauty Vocational and gendered subjectivities in private education for the beauty industry FörordChurchill (?!) lär ha sagt något i stil med: "Går du igenom ett helvete, fortsätt för allt i världen att gå". Han kanske syftade på andra saker än att skriva en avhandling i pedagogik, men för doktoranden själv kan detta vara nog så skräckfyllt och ibland te sig helt omöjligt. I sådana perioder är det avgörande att ha människor omkring sig, både inom och utanför akademin, som på olika sä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Further, studies have compared female students in VET with higher educational preparatory programme girls (Ambjörnsson 2004), or focused on a particular context (e.g. Bredlöv 2018). In contrast, we compared female students associated with different VET programmes, and detected substantial variation in the way they 'were' female students, both between and within the three contexts.…”
Section: Discussionmentioning
confidence: 88%
“…Further, studies have compared female students in VET with higher educational preparatory programme girls (Ambjörnsson 2004), or focused on a particular context (e.g. Bredlöv 2018). In contrast, we compared female students associated with different VET programmes, and detected substantial variation in the way they 'were' female students, both between and within the three contexts.…”
Section: Discussionmentioning
confidence: 88%
“…The findings of this research are parallel to the studies that have been conducted by previous researchers [62], [63], which they found that HBP have a lack of self-confidence to communicate with the customers. High level of self-confidence can help the cosmetology students to communicate well when interacting with the customers [35], [38], [67]. The cosmetology students need to have high self-confidence as they need to provide quality beauty treatment and consultation services to the customers [13], [65].…”
Section: The Factors That Influence the Competency Level Of Communica...mentioning
confidence: 99%
“…In particular, there are several past researchers [9], [19], [34]- [37] found that the competency level of communication skills among the cosmetology students is still at a lower level. Among the factors that cause they have lack of communication skills in the workplace is their weakness in mastering the basic knowledge or theory in cosmetology field [35] and incompetency to transfer the learned theories into a practical form [9]. Whereas, the skills of transferring theory into the practical form will indirectly help in increasing the level of self-confidence among the cosmetologists to communicate with their clients better [38]- [40].…”
Section: Introductionmentioning
confidence: 99%